Fe2+–Mg partitioning between olivine and liquid at low oxygen fugacity: an experimental and thermodynamic framework - Saper, L. M.; Baker, M. B.; Stolper, E. M. (Contributions to Mineralogy and Petrology, 2022)
A set of 1-atm gas-mixing experiments (n = 31) was run using Re wire loops at low-oxygen fugacity (ƒO2, within one half-log unit of the Fe–FeO buffer) and temperatures of 1175–1400 °C to explore the compositional dependence of the Fe2+–Mg olivine–liquid exchange coefficient, $${\mathrm{K}}_{\mathrm{D},{\mathrm{Fe}}^{2+}-\mathrm{Mg}}^{\mathrm{ol}/\mathrm{liq}}$$, under conditions where corrections for liquid Fe3+ are small. The bulk compositions used for these experiments include a picrite, a high-alumina basalt, and a suite of three MORB compositions with variable Fe/Mg. The $${\mathrm{K}}_{\mathrm{D},{\mathrm{Fe}}^{2+}-\mathrm{Mg}}^{\mathrm{ol}/\mathrm{liq}}$$ values from the n = 14 experiments run on pre-saturated Re wire loops were fit to a regular solution model that relates $${\mathrm{K}}_{\mathrm{D},{\mathrm{Fe}}^{2+}-\mathrm{Mg}}^{\mathrm{ol}/\mathrm{liq}}$$ to temperature, melt composition, and olivine composition. Fe2+–Mg exchange in the experiments is well-described using two parameters: the SiO2 content of the liquid and the coexisting olivine composition. Combining our experiments with a literature compilation of low-pressure, low-ƒO2 experiments (largely on non-terrestrial bulk compositions) produced a combined data set spanning a broad region of composition space (e.g., liquid TiO2 and Na2O + K2O contents up to 18.4 wt% and 8.4 wt%, respectively). Fitting this expanded experimental database required two additional liquid compositional terms: Ti, and a Si-(Na + K) cross-term. Because the Fe3+ content of all of the experimental liquids is low, the compositional variation seen in $${\mathrm{K}}_{\mathrm{D},{\mathrm{Fe}}^{2+}-\mathrm{Mg}}^{\mathrm{ol}/\mathrm{liq}}$$is effectively independent of the compositional effects on liquid Fe3+/Fe2+ ratios. Given olivine–liquid Mg or Fe2+ partition coefficient information, it is possible to eliminate the explicit dependence of $${\mathrm{K}}_{\mathrm{D},{\mathrm{Fe}}^{2+}-\mathrm{Mg}}^{\mathrm{ol}/\mathrm{liq}}$$ on olivine composition, enabling a simple iterative approach for calculating the composition of coexisting olivine given only the bulk composition (and Fe3+/Fe2+ ratio) of an olivine-saturated liquid.